Opioids and Chronic Pain: An Analytic Review of the Clinical Evidence - Nadeau, Stephen E.; Wu, Jeffrey K.; Lawhern, Richard A. (Frontiers in Pain Research, 2021)
We conducted an analytic review of the clinical scientific literature bearing on the use of opioids for treatment of chronic non-cancer pain. There is substantial, albeit not definitive, scientific evidence of the effectiveness of opioids in treating pain and of high variability in opioid dose requirements and side effects. The risk of death from opioid treatment involving doses above 100 MMED is approximately 0.25%/year. Multiple large studies refute the concept that short-term use of opioids to treat acute pain predisposes to development of opioid use disorder. The prevalence of opioid use disorder associated with prescription opioids is likely less than 3%. Morbidity, mortality, and financial costs of inadequate treatment of the 18 million Americans with moderate to severe chronic pain are high. Because of the absence of comparative effectiveness studies, there are no scientific grounds for considering alternative nonpharmacologic treatments as an adequate substitute for opioid therapy but these treatments might serve to augment opioid therapy, thereby reducing dosage. There are reasons to question the ostensible risks of co-prescription of opioids and benzodiazepines. As the causes of the opioid crisis have come into focus, it has become clear that the crisis resides predominantly in the streets and that efforts to curtail it by constraining opioid treatment in the clinic are unlikely to succeed.